Colloquial Words Used in "Gossip Girl" Drama Script Written by Cecily Von Ziegesar - Meliana Hardianti; Hartono Hartono (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2014)
An Analysis of the Language Style Used by Barrack Obama and Michelle Obama in Oprah Winfrey Show